UPAYA UNILEVER INDONESIA DALAM PEMBANGUNAN EKONOMI PETANI KEDELAI HITAM INDONESIA MELALUI PROGRAM UNILEVER SUSTAINABLE LIVING PLAN (USLP) TAHUN 2016-2019 - Jibril Surya Ramadhan, (2024)
The discussion of multinational corporations in international relations is one of the discussions that is still ongoing today. As an entity operating in the economic sector, multinational corporations have quite a large influence on a country's economy. PT Unilever Indonesia, Tbk is an MNC that has been established for a long time in Indonesia. In conducting its business in Indonesia, of course PT. Unilever Indonesia Tbk. are obliged to carry out corporate social responsibilities as regulated in law. To make it easier for them to carry out CSR activities, Unilever then formed the Unilever Sustainability Living Plan (USLP) which is a collection of their CSR activities. One of the activities they carry out is empowering black soybean farmers who are one of the important suppliers of the main raw materials for making their products. The problems that exist for black soybean farmers in Indonesia are the lack of interest of farmers in planting black soybeans and marketing which is quite difficult. This research uses a qualitative method with a descriptive model. The final results of this research show that the programs used by Unilever Indonesia in an effort to help the economy of Indonesian black soybean farmers have had a good impact and can have quite a big influence on the black soybean farmers involved.